Análise de arquitetura baseada em nuvem utilizando protocolo MQTT para letramento em braille - Santos, Josimar dos (2023)
In education, social inclusion, necessary to promote the individual development of People with Disabilities (PWD), often requires adaptation to the individual needs of each student. Over the years, technological advancements, techniques, and methodologies have shaped this reality. The increasing use of the Internet of Things (IoT) is connecting devices and expanding sensor networks, enabling the integration of accessibility into people’s daily lives, including the lives of PWD.This work aims to develop an inclusive approach to education, particularly for PWD with visual impairments. We propose a cloud-based architecture, IoT, and the Message Queuing Telemetry Transport (MQTT) protocol for converting text into Braille. Through this cloudbased architecture, our goal is to simplify text-to-Braille conversion, promoting accessibility and providing a dynamic and inclusive learning experience for PWD, with tangible benefits for the educational community, including cost reduction. The framework employs the MQTT protocol to establish communication between devices, enabling interaction through visual and tactile interfaces, as well as voice commands. Additionally, the system operates within a cloud infrastructure, offering scalability and facilitating remote access. After the conversion carried out by the Application Programming Interface (API) in the Python language, a JavaScript Object Notation (JSON) is sent to a tactile display simulator, notifying the user through sounds that reading can commence. While initial experiments conducted in a local environment yielded satisfactory results, project validation will require expansion to real-world experiments with a tactile display prototype.